The impact of the SPEOS method on boosting exclusive breastfeeding rates among postpartum women - Br Karo, Marni; Tamba, Ezra; Simanjuntak, Farida (Svāsthya: Trends in General Medicine and Public Health, 2024)
UNICEF reports that every year, 2.6 million infants worldwide die within their first month of life. One of the determining factors is exclusive breastfeeding. WHO emphasizes the importance of exclusive breastfeeding until 6 months of age without additional food and drink. In Indonesia, the coverage of infants receiving exclusive breastfeeding reached 67.74%, but exclusive breastfeeding is only given to one in two infants under 6 months. Lack of exclusive breastfeeding means infants are not getting adequate nutrition. This study aimed to evaluate the effectiveness of the SPEOS (Stimulation of Endorphin, Oxytocin and Suggestive Massage) method in increasing exclusive breast milk production in postpartum mothers. This study used a quasi-experimental method with a sample of 30 postpartum mothers who were divided into two groups: (1) experimental group that received SPEOS massage method for 10 minutes, and (2) control group that did not receive the intervention. The dependent variable was breast milk production, while the independent variable was massage using the SPEOS method. Data were collected by measuring breast milk volume (ml) and analyzed using t-test. The results showed that the SPEOS method was effective in increasing exclusive breast milk production (p<0.001). The SPEOS method proved to be an effective way to increase exclusive breast milk production in postpartum mothers. The SPEOS method can increase breast milk production, so it needs to be socialized to postpartum mothers by health workers to increase the achievement of exclusive breastfeeding in infants.